Herpetofauna Species Inventory in Harau Valley Natural Tourism Park, 50 Kota Regency, West Sumatra. - Fachrul Rozi Octavian; Fitra Nugraha (Jurnal Serambi Biologi, 2022)
The purpose of this study was to find amphibians and reptiles that live in the Harau Valley TWA, West Sumatra province. Because this area serves as a natural tourist attraction, it still maintains the primary forests that exist in most areas that may provide decent homes for herpetofuna groups or other types of animals. The survey was conducted from April to May 2022. From the survey that has been carried out, 10 species of amphibians are found which belong to 5 families and 7 species of reptiles which are classified as 5 families. The study area will be a worthy place to conduct biological and ecological research in the future.